The dawn of a new ice age: social egg freezing. (4th April 2018) - Jones, Benjamin P.; Saso, Srdjan; Mania, Anastasia; Smith, J. Richard; Serhal, Paul; Ben Nagi, Jara
Abstract: Given the age‐related decline in ovarian reserve and oocyte quality, it is unsurprising the global trend of deferring motherhood has resulted in increased levels of involuntary childlessness. The development of oocyte vitrification, with pregnancy and livebirth rates now comparable to using fresh oocytes, has provided an opportunity to cryopreserve oocytes electively for future use, empowering women with the capacity to delay their childbearing years. While it enhances reproductive autonomy, age‐related obstetric complications, economic implications and the risk of unsuccessful future treatment make this a controversial therapeutic option. However, some women have no reasonable alternative, such as single women approaching their late thirties, in whom egg freezing, although not a guarantee against involuntary childlessness, offers hope by extending the window of opportunity to find a partner. Given the upward trend in women electively cryopreserving their eggs, it would appear that a new ice age, from a fertility perspective, is upon us.